Analysis of word number and content in discourse of patients with mild to moderate Alzheimer's disease - Lira,Juliana Onofre de (2014)
Alzheimer's disease (AD) is characterized by impairments in memory and other cognitive functions such as language, which can be affected in all aspects including discourse. A picture description task is considered an effective way of obtaining a discourse sample whose key feature is the ability to retrieve appropriate lexical items. There is no consensus on findings showing that performance in content processing of spoken discourse deteriorates from the mildest phase of AD.OBJECTIVE:To compare the quantity and quality of discourse among patients with mild to moderate AD and controls.METHODS: A cross-sectional study was designed. Subjects aged 50 years and older of both sexes, with one year or more of education, were divided into three groups: control (CG), mild AD (ADG1) and moderate AD (ADG2). Participants were asked to describe the "cookie theft" picture. The total number of complete words spoken and information units (IU) were included in the analysis.RESULTSThere was no significant difference among groups in terms of age, schooling and sex. For number of words spoken, the CG performed significantly better than both the ADG 1 and ADG2, but no difference between the two latter groups was found. CG produced almost twice as many information units as the ADG1 and more than double that of the ADG2. Moreover, ADG2 patients had worse performance on IUs compared to the ADG1.CONCLUSIONDecreased performance in quantity and content of discourse was evident in patients with AD from the mildest phase, but only content (IU) continued to worsen with disease progression.